2018
DOI: 10.1111/epi.14438
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in epilepsy: A potential biomarker of sudden unexpected death in epilepsy risk

Abstract: These findings suggest that autonomic dysfunction is associated with SUDEP risk in patients with epilepsy due to sodium channel mutations. The relationship of HRV to SUDEP merits further study; HRV may eventually have potential as a biomarker of SUDEP risk, which would allow for more informed counseling of patients and families, and also serve as a useful outcome measure for research aimed at developing therapies and interventions to reduce SUDEP risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 37 publications
4
84
1
2
Order By: Relevance
“…90 Recently, one group showed that heart rate variability was decreased among cases of SUDEP versus individuals with epilepsy, indicating autonomic dysfunction. 8 This was consistent with earlier evidence of a correlation between SUDEP risk and lower RMSSD (Root Mean Square of Successive Differences), reflecting depressed vagal modulation of heart rate variability. 91 However, other studies comparing suspected SUDEP cases with matched epilepsy controls revealed no difference in resting ECG measures or heart rate variability.…”
Section: Clinical Significance Of Altered Cardiac Ion Channel Expresupporting
confidence: 91%
See 3 more Smart Citations
“…90 Recently, one group showed that heart rate variability was decreased among cases of SUDEP versus individuals with epilepsy, indicating autonomic dysfunction. 8 This was consistent with earlier evidence of a correlation between SUDEP risk and lower RMSSD (Root Mean Square of Successive Differences), reflecting depressed vagal modulation of heart rate variability. 91 However, other studies comparing suspected SUDEP cases with matched epilepsy controls revealed no difference in resting ECG measures or heart rate variability.…”
Section: Clinical Significance Of Altered Cardiac Ion Channel Expresupporting
confidence: 91%
“…Similarly, QTc dispersion (variability) was found to incrementally increase the risk of sudden cardiac death . Recently, one group showed that heart rate variability was decreased among cases of SUDEP versus individuals with epilepsy, indicating autonomic dysfunction . This was consistent with earlier evidence of a correlation between SUDEP risk and lower RMSSD (Root Mean Square of Successive Differences), reflecting depressed vagal modulation of heart rate variability .…”
Section: Clinical Significance Of Altered Cardiac Ion Channel Expresssupporting
confidence: 79%
See 2 more Smart Citations
“…It is possible to find numerous works in which these signals are used to detect stress, emotions, and activity in the literature. The ECG signal is used in some papers such as [23], where the obtained results suggest that positive emotions lead to alterations in HRV, which may be beneficial in some illness treatment [19,31,32].…”
mentioning
confidence: 99%